2018
DOI: 10.1016/j.ijheatmasstransfer.2017.11.045
|View full text |Cite
|
Sign up to set email alerts
|

A point sink superposition method for predicting droplet interaction effects during vapor-diffusion-driven dropwise condensation in humid air

Abstract: During dropwise condensation from the ambient environment, water vapor present in air must diffuse to the surface of each droplet. The spatial distribution of water vapor in the local surroundings of each individual droplet determines the total condensation rate. However, available models for dropwise condensation in humid air assume that such systems of droplets grow either as an equivalent film or that the growth of each droplet is completely isolated; the interactions between droplets are poorly described a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 27 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…However, since most gas molecules exist in a high concentration near the central axis, several nanodroplets are generated and are in contact with one another. 62,63 As shown in a cryo-SEM image, their contact coalesces into large microdroplets near the center. 63,64 Consequently, the diameter of the droplets decreased as its position moved radially outward where droplets had rarely coalesced.…”
Section: Resultsmentioning
confidence: 99%
“…However, since most gas molecules exist in a high concentration near the central axis, several nanodroplets are generated and are in contact with one another. 62,63 As shown in a cryo-SEM image, their contact coalesces into large microdroplets near the center. 63,64 Consequently, the diameter of the droplets decreased as its position moved radially outward where droplets had rarely coalesced.…”
Section: Resultsmentioning
confidence: 99%
“…This has been done using the point sink superposition method (Figure 4c). [92,93] Based on the present literature, I believe that particularly three recurring themes are currently limiting the full utilization of spatial control. These are 1) their issues with robustness, 2) their fixed behavior, and 3) only spatial control of water is considered.…”
Section: Vapor Sinks and Depletion Zonesmentioning
confidence: 95%
“…The point sink superposition method solves for the diffusion of vapor within the air domain surrounding the droplets during dropwise condensation. Our previous work [15] provides a complete description of the method which is briefly summarized here. The model assumes: (i) droplets can be treated as point sinks located at the droplet centers, (ii) the condensation process can be treated as quasi-steady state, (iii) there is negligible thermal resistance across the droplets (i.e., the temperature at the surface of the droplet is equal to the temperature of the substrate), (iv) the contact angle of the droplets is independent of droplet size, and (v) changes in vapor concentration at the surface of the droplets due to curvature are negligible.…”
Section: The Point Sink Superposition Methods (Pssm)mentioning
confidence: 99%
“…At later times, droplets that have polygons with larger areas do not necessarily grow faster. We have previously shown that the condensation rate of pairs of droplets predicted by the PSSM is sensitive to the ratio of between the droplet sizes [15]. Large droplets can limit the vapor diffusion to small droplets in their surroundings For example, droplet h in Figure 9 (b) has a larger Voronoi polygon area than its neighbor droplet l , but grows at a smaller rate, because droplet l has a larger size and it is surrounded by smaller neighbors than droplet h .…”
Section: Effects Of Droplet Size and Spatial Distribution On The Condmentioning
confidence: 97%
See 1 more Smart Citation